A novel multimode sensor showing cation-dependent fluorescence colour. Issue 42 (23rd October 2017) - Fujii, Sho; Ishimura, Ryo; Nakagawa, Atsushi; Kitamura, Noboru
Abstract : We developed a novel fluorescent metal sensor, by which nature of a metal cation could be identified directly by the fluorescence colour. Abstract : A novel sensor, 4-[2-(9-anthryl)ethynyl]-1, 10-phenanthroline (1 ), exhibits highly intense fluorescent in the wavelength region of 440–600 nm (maximum wavelength ( λ f ) = 470 nm) with the quantum yield ( Φ f ) and lifetime ( τ f ) being 0.90 and 4.2 ns, respectively, in CH3 CN at 298 K. In the presence of a divalent cation (M 2+ = Ba 2+, Ca 2+, Mg 2+, or Zn 2+ ) in CH3 CN, sensor1 can tightly bind M 2+ and shows intense fluorescent ( Φ f = 0.90–0.19, τ f = 2.1–6.9 ns) with the color being dependent on the nature of M 2+ ( λ f = 514–584 nm). The results demonstrate that a single fluorescent sensor1 is capable of simultaneous identification and quantitation of M 2+ based on λ f and the fluorescent intensity ( Φ f ), respectively. The fluorescence maximum energy of the [1 –M 2+ ] complex is shown to correlate linearly with the p K a value of M 2+ . The spectroscopic and photophysical properties of sensor1 in the absence and presence of M 2+ are also discussed.